(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
In this paper are explored the mechanical (ultimate compression strength, ultimate strain, Young’s modulus, hardness) and the electrical (relative permittivity, specific electrical resistance, quality factor, their dependence on the electric field frequency in the range till 1MHz) properties of the solid sapropel. For the researches are used samples from the solid, monolith sapropel (obtained in the drying process) and samples from the sapropel powder that are pressed with a different force; before the measurements, a part of these samples were heated. There is explored the dependence of the relative permittivity on temperature. Are explored the methods for the forming of the products from the solid sapropel powder.